1999
DOI: 10.1182/blood.v94.12.3986.424k18_3986_3996
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Configuration of Rh D Epitopes as Defined by Site-Directed Mutagenesis and Expression of Mutant Rh Constructs in K562 Erythroleukemia Cells

Abstract: The Rh D antigen is the most clinically important protein blood group antigen of the erythrocyte. It is expressed as a collection of at least 37 different epitopes. The external domains of the Rh D protein involved in epitope presentation have been predicted based on the analysis of variant Rh D protein structures inferred from their cDNA sequences and their D epitope expression. This analysis can never be absolute because (1) most partial D phenotypes involve multiple amino acid changes in the Rh D protein an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0
2

Year Published

2001
2001
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 33 publications
3
33
0
2
Order By: Relevance
“…The Rh D antigen contains at least 37 different epitopes. Site-directed mutagenesis experiments to study the expression of different D epitopes have identified nine critical amino acids, giving rise to at least six distinct epitope clusters involving one or more of the six external loops of the Rh D polypeptide (Liu et al, 1999) Competitive EIA of monoclonal IgG anti-D 157 4 and 6. Loops 3 and 4 (or all 3 loops in some cases) appear to be required for expression of the most clinically significant epitope, epD6/7, as defined in the original 1-9 epitope model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Rh D antigen contains at least 37 different epitopes. Site-directed mutagenesis experiments to study the expression of different D epitopes have identified nine critical amino acids, giving rise to at least six distinct epitope clusters involving one or more of the six external loops of the Rh D polypeptide (Liu et al, 1999) Competitive EIA of monoclonal IgG anti-D 157 4 and 6. Loops 3 and 4 (or all 3 loops in some cases) appear to be required for expression of the most clinically significant epitope, epD6/7, as defined in the original 1-9 epitope model.…”
Section: Discussionmentioning
confidence: 99%
“…However, just three amino acids located in loop 6 are predicted to give rise to epD3 (although other residues may be necessary to stabilize the configuration). The proposition by Liu et al (1999) that loops 3 and 6 are nonadjacent may account for the very limited ability of the epD3.1reactive MoAbs 1-73 and 1-96 to inhibit the binding of biotinylated BRAD-5, rather than that these MoAbs are poor binders, as their estimated potencies using flow cytometry were 6Á4 and 11Á4 IU mg À1 . Although the four epD6.8-reactive MoAbs, including BRAD-5 itself, had high specific activities, they were not the most potent MoAbs in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic analysis has also found antithetical C/c and E/e core epitopes in the polymorphic amino acid change at the second and fourth loops, respectively [20]. Recently, expression analysis of recombinant Rh polypeptides and band3 glycoprotein was performed on erythroleukemic cell lines, and fine mapping of RhD epitopes became available [21][22][23][24][25]. The use of the recombinant antigen system in analysis is advantageous because of the selective expression of any particular antigen, independent of epitope conformation.…”
Section: Introductionmentioning
confidence: 99%
“…No epitopes were mapped on loop 5. Site-directed mutagenesis [20] has shown that the external domains of the RhD protein are transduced into the RhcE polypeptide and the expression of D epitopes has been studied. That study revealed loop-loop interactions of the RhD polypeptide.…”
Section: Discussionmentioning
confidence: 99%